2008
DOI: 10.1029/2008jd009901
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ENSO and northward propagating intraseasonal oscillation in the east Asian summer monsoon system

Abstract: [1] Observational studies are presented on the relationship between El Niño-Southern Oscillation (ENSO) and the northward propagating intraseasonal oscillation (NPISO) in the east Asian summer monsoon (EASM) system. The summer NPISO activity shows a significant correlation with the preceding winter extreme phase of ENSO cycles. A higher correlation appears during late summer, which is consistent with frequent heavy rainfall events at that time as revealed in some previous case studies. The westward expansion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 55 publications
3
40
0
1
Order By: Relevance
“…As a result, the remote IOSST warming and local western Pacific SST cooling are key factors in bridging the ENSO into the WNPSH and, in turn, EASM. The summertime NPISO activity is also strongly related to IOSST warming and western Pacific cooling that follows a warm ENSO event (Yun et al, 2008). As evidence of the significant NPISO-ENSO relationship, the summertime low-level height anomalies regressed onto the ENSO phase during November to January (Figure 10(a)) reveal enhanced WNP anticyclonic and northern cyclonic anomalies similar to the NPISO-induced three-cell circulation structure shown in Figure 9.…”
Section: Interannual Relationship Between Npiso and Ensomentioning
confidence: 65%
See 2 more Smart Citations
“…As a result, the remote IOSST warming and local western Pacific SST cooling are key factors in bridging the ENSO into the WNPSH and, in turn, EASM. The summertime NPISO activity is also strongly related to IOSST warming and western Pacific cooling that follows a warm ENSO event (Yun et al, 2008). As evidence of the significant NPISO-ENSO relationship, the summertime low-level height anomalies regressed onto the ENSO phase during November to January (Figure 10(a)) reveal enhanced WNP anticyclonic and northern cyclonic anomalies similar to the NPISO-induced three-cell circulation structure shown in Figure 9.…”
Section: Interannual Relationship Between Npiso and Ensomentioning
confidence: 65%
“…In particular, Yun et al (2008) reported a significant relationship between ENSO and NPISO over East Asia. Because the northward migration of the East Asian monsoonal front is modulated by a 30-60 day ISO (Chen and Chen, 1995;Yun et al, 2009), compared to the total variability in EASM, the ISO is more significantly related to ENSO.…”
Section: Interannual Relationship Between Npiso and Ensomentioning
confidence: 99%
See 1 more Smart Citation
“…The positive SAM-EAM relationship is mainly influenced by a wave propagating over Tropics along the lower-level monsoon westerly (Wang et al 2001, 2013, Hsu and Lin 2007Liu et al 2008;Yun et al 2008Yun et al , 2010Lee et al 2011aLee et al , b, 2013) that preferentially occurs during the decaying phase of the ENSO (Ding et al 2010;Lee et al 2011a, b;Wang et al 2013Wang et al , 2015Chen et al 2016;Ha et al 2017). The tropical teleconnection is called the western North Pacific-North America (WPNA) pattern, including the WPSH as an important factor bridging the SAM and EAM climate (Wang et al 2001;Kosaka et al 2013;Lee et al 2013a, b).…”
Section: Decaying Ensomentioning
confidence: 99%
“…Sea surface temperature anomaly (SSTA) and local air-sea interaction were suggested to be the main factors in contribution to the interannual variation of the WNPSH [e.g., Yang et al, 2007;Yun et al, 2008]. The WNP, the maritime continent, the northern Indian Ocean (NIO), and the equatorial eastern Pacific where El Niño-Southern Oscillation (ENSO) occurs were the critical regions where the SSTA has notable local or remote effect on the interannual variation of the WNPSH in boreal summer [e.g., Wu et al, 2010;Yun et al, 2013;Wang et al, 2013].…”
Section: Introductionmentioning
confidence: 99%